Micro-expansive internal curing agent for steel pipe self-compacting concrete and preparation method of micro-expansive internal curing agent

By using water-retaining gel microbeads formed by sulfur-solid ash and polymer materials in steel pipe self-filled concrete, the problem of poor controllability of traditional internal curing agents is solved, and the concrete is efficient Improved water retention and compressive strength.

CN119430731APending Publication Date: 2025-02-14SICHUAN HUASHI GREEN HOMELAND BUILDING MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411715434.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The water absorption and expansion time and water release time of traditional internal curing agents are not controllable, which affects the compressive strength and working performance of concrete, resulting in slow development of internal curing agents.

Method used

The solid sulfur ash is used as the internal curing agent matrix to reduce the early shrinkage performance of the solid sulfur ash itself, and use polymer materials such as alginate, polyacrylamide, carboxymethylcellulose ether to form a core-shell structure. Water-retaining gel microbeads improve the water absorption and water retention properties of internal curing agents.

Benefits of technology

It realizes the maintenance of internal humidity of concrete, reduces early shrinkage performance, improves compressive strength and working performance, and extends the effective use time of internal curing agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156779510000091
    Figure BDA0005156779510000091
Patent Text Reader

Abstract

The invention discloses a micro-expansive internal curing agent for steel pipe self-compacting concrete and a preparation method thereof.The micro-expansive internal curing agent comprises fluidized bed combustion ash and an adhesive component, the fluidized bed combustion ash is soaked in an adhesive solution, and the adhesive component is coated on the surface and in pores of the fluidized bed combustion ash; the mass fraction of viscose components in the viscose solution is 0.1%-1%, and the viscose components comprise 0-80 parts of alginate, 5-30 parts of polyacrylamide and 0-20 parts of carboxymethyl cellulose ether. According to the internal curing agent, the fluidized bed combustion ash is adopted as an internal curing agent matrix, the fluidized bed combustion ash is composed of calcium sulfate and the like, the early shrinkage performance of concrete can be reduced through expansion of the fluidized bed combustion ash, meanwhile, the surface porosity characteristic of the fluidized bed combustion ash is utilized, and viscose formed after alginate, polyacrylamide and carboxymethyl cellulose ether are dissolved in water is combined; pores of the fluidized bed combustion ash are filled with components such as alginate and the like, and the components are crosslinked with calcium ions on the surface of the fluidized bed combustion ash to form water-retaining gel microspheres with core-shell structures, so that the water absorption and water retention properties of the internal curing agent are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, and in particular to a micro-expansion type internal curing agent for steel pipe self-compacting concrete and a preparation method thereof. Background Art

[0002] Steel tube self-compacting concrete structure is a new type of structure that combines steel tubes and concrete. In addition to meeting the performance requirements of strength, durability, workability, etc., steel tube self-compacting concrete has high requirements for concrete shrinkage performance. The volume shrinkage after the concrete hardens makes it impossible for the concrete to be tightly combined with the steel tube wall, which is prone to problems such as debonding and degassing. Concrete is enclosed inside the steel tube, so it is very effective to add internal curing agent as a long-term water supply source. The internal curing agent of concrete refers to the internal water source provided by adding water-absorbing materials to the concrete. This type of water-absorbing material can adjust and convert the storage and water release functions according to external conditions. The water-absorbing material in the concrete can continuously release water to the surrounding area to replenish the internal water consumption of the cement stone, so that there is enough water inside the concrete for secondary hydration, thereby effectively reducing the shrinkage. Commonly used internal curing agents include highly absorbent resins, porous ceramsite, diatomaceous earth, etc. However, the water absorption and expansion time and water release time of traditional internal curing agents are not controllable, and have a significant impact on the workability and mechanical properties of concrete, thus limiting the development of internal curing agents in concrete.

[0003] In view of this, this application is hereby filed. Summary of the invention

[0004] The problem with the prior art is that the water absorption and expansion time and water release time of the traditional internal curing agent are not controllable, and have a significant impact on the compressive strength and workability of the concrete, thus resulting in the slow development of the internal curing agent. The present invention provides a micro-expansion type internal curing agent for self-compacting concrete of steel pipes and a preparation method thereof, which uses solid sulfur ash as the matrix of the internal curing agent, and utilizes the solid sulfur ash to have components such as calcium sulfate. Through the expansion of the solid sulfur ash itself, the early shrinkage performance of the concrete can be reduced. At the same time, the porous properties of the surface of the solid sulfur ash are utilized, combined with alginate, polyacrylamide, carboxymethyl cellulose ether and water to form a viscose, so that components such as alginate are filled in the pores of the solid sulfur ash, and cross-linked with the calcium ions on the surface of the solid sulfur ash to form water-retaining gel microbeads with a core-shell structure, thereby achieving the water absorption and water retention performance of the internal curing agent and ensuring the internal humidity of the concrete.

[0005] The present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a micro-expansion internal curing agent, comprising solid sulfur ash and a viscose component, wherein the solid sulfur ash is immersed in a viscose solution so that the viscose component is coated on the surface and pores of the solid sulfur ash;

[0007] The mass fraction of the viscose component in the viscose solution is 0.1% to 1%, and the viscose component includes 0 to 80 parts of alginate, 5 to 30 parts of polyacrylamide, and 0 to 20 parts of carboxymethyl cellulose ether.

[0008] Sulfur-fixing ash refers to the solid waste discharged after sulfur-containing coal and sulfur-fixing agent are mixed in a certain proportion and burned in a fluidized bed to fix sulfur. The surface of sulfur-fixing ash particles is rough and irregular, and there are a large number of pores. Therefore, sulfur-fixing ash has a strong water demand. At the same time, sulfur-fixing ash contains active calcium oxide, calcium sulfate and other components, so it has micro-expansion properties; and sulfur-fixing ash has volcanic ash activity and self-hardening properties, and its application in concrete preparation can improve the strength of concrete. Therefore, the internal curing agent of the present invention adopts sulfur-fixing ash as the matrix, and utilizes the components of sulfur-fixing ash such as calcium sulfate. Through the expansion of sulfur-fixing ash itself, the early shrinkage performance of concrete can be reduced.

[0009] Alginate is an industrial byproduct. It forms a stable viscous gel after being dissolved in water. It has slight water absorption. It can form gel microbeads with calcium ions. It has strong water absorption, can continuously provide water for hydration, and to a certain extent block large capillaries. The hydrogels formed by high molecular copolymers such as polyacrylamide, carboxymethyl cellulose ether and alginate with calcium ions are all single-ion network gels. The swelling properties, mechanical strength, adsorption and other properties of single-ion network gels are poor. Through the physical compounding of different copolymers, a hydrogel with a three-dimensional porous network structure is formed, which can not only lock a large amount of water, but also has good mechanical strength, fatigue resistance, adsorption and other properties.

[0010] Therefore, the present invention adopts polyacrylamide, carboxymethyl cellulose ether and alginate as the compound, and utilizes the porous characteristics of the surface of solid sulfur ash at the same time. Through the viscose formed by the dissolution of alginate, polyacrylamide, carboxymethyl cellulose ether and water, alginate, polyacrylamide and carboxymethyl cellulose ether are filled in the pores of the solid sulfur ash, and the alginate, polyacrylamide and carboxymethyl cellulose ether are cross-linked with the calcium ions on the surface of the solid sulfur ash to form water-retaining gel microbeads with a core-shell structure. The gel microbeads have good water absorption and water retention properties, thereby solving the problem of water shortage maintenance of concrete in a closed environment and solving the problems of debonding and degassing of steel pipe self-compacting concrete.

[0011] At present, there is also a technical solution that uses solid sulfur ash as an internal curing agent. However, in order to isolate water and avoid early reaction between water and solid sulfur ash, a masking agent and a water-retaining substance need to be added. The water-retaining substance is only physically adsorbed on the surface of the pores, so the adhesion is low and the water retention performance is poor. The present invention uses an alginate-polyacrylamide-carboxymethyl cellulose ether composite adhesive component that can complex with calcium ions in the solid sulfur ash to form core-shell structure water-retaining microbeads, so that chemical adsorption is formed between it and the solid sulfur ash, and the adhesion is high, which greatly improves the water retention. At the same time, the alginate-polyacrylamide-carboxymethyl cellulose ether composite adhesive component can automatically form a layer of adhesive film covering the surface of the solid sulfur ash particles, thereby playing a masking role, which can prevent the solid sulfur ash from reacting with water prematurely in the early stage of cement hydration. Polyacrylamide and carboxymethyl cellulose ether can improve the stability and water retention of the gel microbeads formed by alginate and calcium, and realize the continuous water loss of the internal curing agent in the later stage.

[0012] The internal curing agent adopted by the present invention has the following characteristics: in the early stage of cement hydration, the gel microbeads on the surface of the solid sulfur ash absorb water first to avoid reaction with the solid sulfur ash; when the hydration proceeds to a certain extent, the gel microbeads begin to lose water and then rupture under the action of strong alkalinity and high temperature, thereby maintaining the humidity inside the concrete; at the same time, after the gel microbeads rupture, the calcium sulfate component inside the solid sulfur ash reacts with water to expand, fills the pores inside the concrete, and reduces the early shrinkage of the concrete.

[0013] In a specific embodiment, the viscose solution further comprises sodium thiosulfate in an amount of 0.1% to 3% by mass.

[0014] In a specific embodiment, the viscose solution further comprises 30% to 70% by mass of ethanol.

[0015] In a specific embodiment, the viscose solution further comprises 0.5% to 1% by mass of sodium gluconate.

[0016] In a specific embodiment, the viscose solution further comprises sodium pyrosulfite in an amount of 0.1% to 0.8% by mass.

[0017] The present invention adopts sodium thiosulfate and ethanol as auxiliary solvents of the adhesive component, and simultaneously adopts sodium gluconate and sodium pyrosulfite as dispersants of the adhesive component, which can improve the uniform dispersion of alginate in the pores of the solid sulfur ash matrix and enhance the adhesion between the alginate and the solid sulfur ash.

[0018] In a specific embodiment, the mass ratio of the solid sulfur ash to the viscose solution is 1:50-100.

[0019] In a specific embodiment, the alginate is one or more of sodium alginate, potassium alginate, ultra-low viscosity sodium alginate, ultra-low viscosity potassium alginate, ultra-high viscosity sodium alginate and ultra-high viscosity potassium alginate.

[0020] In a third aspect, the present invention provides a method for preparing a micro-expansion type internal curing agent, comprising the following steps:

[0021] (1) dissolving sodium thiosulfate in water to prepare a solution, and then adding alginate, polyacrylamide, and carboxymethyl cellulose ether into the solution and stirring to obtain a uniformly mixed viscose latex;

[0022] (2) adding sodium gluconate and sodium pyrosulfite to the viscose emulsion and stirring, and after dissolving, pouring into ethanol and stirring to obtain a viscose solution;

[0023] (3) Pour the solid sulfur ash powder into the pre-viscosity solution, continue stirring and let it stand;

[0024] (4) filtering the soaked solid sulfur ash powder, dehydrating and drying it to obtain a micro-expandable solid sulfur ash-based internal curing agent.

[0025] In a specific embodiment, the stirring condition of the solution in step (1) is 30-50° C. and continuous stirring for 1-2 hours;

[0026] The stirring condition of the solution in step (2) is to add sodium gluconate and sodium pyrosulfite and stir for 5 to 10 minutes, and after dissolution, pour into ethanol and stir for 10 to 40 seconds;

[0027] The stirring condition of the solution in step (3) is to stir for 20 to 50 minutes and then stand for 1 to 3 hours.

[0028] In a third aspect, the present invention provides a steel tube self-compacting concrete, comprising the following components in parts by mass: 350-450 parts of cement, 50-110 parts of fly ash, 10-30 parts of mineral powder, 20-40 parts of silica fume, 600-1000 parts of sand, 700-1200 parts of stone, 4-9 parts of admixture, and 30-60 parts of micro-expansive sulfur-fixing ash-based internal curing agent.

[0029] In a specific embodiment, preferably, the steel tube self-compacting concrete includes the following components in parts by mass: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, and 60 parts of micro-expansive sulfur-fixing ash-based internal curing agent.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] 1. A micro-expansion type internal curing agent for self-compacting concrete of steel pipe and a preparation method thereof are provided in an embodiment of the present invention. The surface of the solid sulfur ash particles is rough and irregular, and there are a large number of pores, so it has a strong water demand. At the same time, the solid sulfur ash contains active calcium oxide, calcium sulfate and other components, so it has micro-expansion performance. Therefore, the solid sulfur ash is used as the matrix of the internal curing agent. The solid sulfur ash has the components of calcium sulfate and the like. Through the expansion of the solid sulfur ash itself, the early shrinkage performance of the concrete can be reduced.

[0032] 2. A micro-expansion type internal curing agent for self-compacting concrete of steel pipe and a preparation method thereof provided in an embodiment of the present invention adopts polyacrylamide, carboxymethyl cellulose ether and sodium alginate as compound, and utilizes the porous characteristics of the surface of solid sulfur ash, through the viscose formed by the dissolution of alginate, polyacrylamide, carboxymethyl cellulose ether and water, so that alginate, polyacrylamide and carboxymethyl cellulose ether are filled in the pores of solid sulfur ash, and cross-linked with calcium ions on the surface of solid sulfur ash to form water-retaining gel microbeads with a core-shell structure. The gel microbeads have good water absorption and water retention properties, thereby preventing concrete from losing water under high alkalinity and high temperature conditions;

[0033] 3. A micro-expansive internal curing agent for self-compacting concrete of steel pipes and a preparation method thereof provided in an embodiment of the present invention adopts alginate-polyacrylamide and carboxymethyl cellulose ether composite adhesive components that can form core-shell structure water-retaining microbeads with calcium ions in solid sulfur ash by complexation, and form chemical adsorption with solid sulfur ash, with high adhesion, greatly improving water retention. At the same time, the composite adhesive components of alginate, polyacrylamide and carboxymethyl cellulose ether can automatically form a layer of adhesive film covering the surface of solid sulfur ash particles, thereby playing a masking role, and can prevent the solid sulfur ash from reacting with water in the early stage of cement hydration;

[0034] 4. A micro-expansive internal curing agent for self-compacting concrete of steel pipe and a preparation method thereof provided in an embodiment of the present invention utilizes solid sulfur ash of solid waste and sodium alginate, an industrial by-product, fully utilizes industrial solid waste, avoids secondary treatment of industrial waste residue, improves waste residue utilization rate, and realizes resource recycling;

[0035] 5. A micro-expansive internal curing agent for self-compacting concrete of a steel pipe and a preparation method thereof provided in an embodiment of the present invention, wherein the internal curing agent is prepared by compounding sodium alginate and solid sulfur ash, thereby improving the porous water absorption performance of the solid sulfur ash and reducing the influence of the internal curing agent on the working performance, compressive strength and durability of the concrete;

[0036] 6. An embodiment of the present invention provides a micro-expansive internal curing agent for steel tube self-compacting concrete and a preparation method thereof. The internal curing agent is prepared by compounding a composite adhesive component of sodium alginate, polyacrylamide, and carboxymethyl cellulose ether with solid sulfur ash. The water absorption and water release time of the internal curing agent can be effectively controlled, the water absorption and water retention performance of the concrete can be improved, water can be released continuously, the reaction of the expansion agent of the steel tube self-compacting concrete can be ensured, the shrinkage of the concrete can be reduced, and the debonding and degassing of the steel tube self-compacting concrete can be avoided. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0038] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known materials or methods are not specifically described.

[0039] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0040] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0041] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0042] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0043] In a first aspect, the present invention provides a micro-expansion internal curing agent, comprising solid sulfur ash and a viscose component, wherein the solid sulfur ash is soaked in a viscose solution so that the viscose component is coated on the surface and pores of the solid sulfur ash;

[0044] The mass fraction of the viscose component in the viscose solution is 0.1% to 1%, and the viscose component includes 0 to 80 parts of alginate, 5 to 30 parts of polyacrylamide, and 0 to 20 parts of carboxymethyl cellulose ether.

[0045] Sulfur-fixing ash refers to the solid waste discharged after sulfur-containing coal and sulfur-fixing agent are mixed in a certain proportion and burned in a fluidized bed to fix sulfur. The surface of sulfur-fixing ash particles is rough and irregular, and there are a large number of pores. Therefore, sulfur-fixing ash has a strong water demand. At the same time, sulfur-fixing ash contains active calcium oxide, calcium sulfate and other components, so it has micro-expansion properties; and sulfur-fixing ash has volcanic ash activity and self-hardening properties, and its application in concrete preparation can improve the strength of concrete. Therefore, the internal curing agent of the present invention adopts sulfur-fixing ash as the matrix, and utilizes the components of sulfur-fixing ash such as calcium sulfate. Through the expansion of sulfur-fixing ash itself, the early shrinkage performance of concrete can be reduced.

[0046] Alginate is an industrial byproduct. It forms a stable viscous gel after being dissolved in water. It has slight water absorption. It can form gel microbeads with calcium ions. It has strong water absorption, can continuously provide water for hydration, and to a certain extent block large capillaries. The hydrogels formed by high molecular copolymers such as polyacrylamide, carboxymethyl cellulose ether and alginate with calcium ions are all single-ion network gels. The swelling properties, mechanical strength, adsorption and other properties of single-ion network gels are poor. Through the physical compounding of different copolymers, a hydrogel with a three-dimensional porous network structure is formed, which can not only lock a large amount of water, but also has good mechanical strength, fatigue resistance, adsorption and other properties.

[0047] Therefore, the present invention adopts polyacrylamide, carboxymethyl cellulose ether and sodium alginate as the compound, and utilizes the porous characteristics of the surface of solid sulfur ash at the same time. Through the viscose formed by the dissolution of alginate, polyacrylamide, carboxymethyl cellulose ether and water, alginate, polyacrylamide and carboxymethyl cellulose ether are filled in the pores of the solid sulfur ash, and the alginate, polyacrylamide and carboxymethyl cellulose ether are cross-linked with the calcium ions on the surface of the solid sulfur ash to form water-retaining gel microbeads with a core-shell structure. The gel microbeads have good water absorption and water retention properties, thereby preventing the concrete from losing water under high alkalinity and high temperature conditions, and solving the problems of debonding and degassing of steel pipe self-compacting concrete.

[0048] At present, there is also a technical solution that uses solid sulfur ash as an internal curing agent. However, in order to isolate water and avoid early reaction between water and solid sulfur ash, a masking agent and a water-retaining substance need to be added. The water-retaining substance is only physically adsorbed on the surface of the pores, so the adhesion is low and the water retention performance is poor. The present invention uses an alginate-polyacrylamide-carboxymethyl cellulose ether composite adhesive component that can complex with calcium ions in the solid sulfur ash to form core-shell structure water-retaining microbeads, so that chemical adsorption is formed between it and the solid sulfur ash, and the adhesion is high, which greatly improves the water retention. At the same time, the alginate-polyacrylamide-carboxymethyl cellulose ether composite adhesive component can automatically form a layer of adhesive film covering the surface of the solid sulfur ash particles, thereby playing a masking role, which can prevent the solid sulfur ash from reacting with water in the early stage of cement hydration. Polyacrylamide and carboxymethyl cellulose ether can improve the stability and water retention of the gel microbeads formed by alginate and calcium, and realize the continuous water loss of the internal curing agent in the later stage.

[0049] The internal curing agent adopted by the present invention has the following characteristics: in the early stage of cement hydration, the gel microbeads on the surface of the solid sulfur ash absorb water first to avoid reaction with the solid sulfur ash; when the hydration proceeds to a certain extent, the gel microbeads begin to lose water and then rupture under the action of strong alkalinity and high temperature, thereby maintaining the humidity inside the concrete; at the same time, after the gel microbeads rupture, the calcium sulfate component inside the solid sulfur ash reacts with water to expand, fills the pores inside the concrete, and reduces the early shrinkage of the concrete.

[0050] In a specific embodiment, the viscose solution further comprises sodium thiosulfate in an amount of 0.1% to 3% by mass.

[0051] In a specific embodiment, the viscose solution further comprises 30% to 70% by mass of ethanol.

[0052] In a specific embodiment, the viscose solution further comprises 0.5% to 1% by mass of sodium gluconate.

[0053] In a specific embodiment, the viscose solution further comprises sodium pyrosulfite in an amount of 0.1% to 0.8% by mass.

[0054] The present invention adopts sodium thiosulfate and ethanol as auxiliary solvents of the adhesive component, and simultaneously adopts sodium gluconate and sodium pyrosulfite as dispersants of the adhesive component, which can improve the uniform dispersion of alginate in the pores of the solid sulfur ash matrix and enhance the adhesion between the alginate and the solid sulfur ash.

[0055] In a specific embodiment, the mass ratio of the solid sulfur ash to the viscose solution is 1:50-100.

[0056] In a specific embodiment, the alginate is one or more of sodium alginate, potassium alginate, ultra-low viscosity sodium alginate, ultra-low viscosity potassium alginate, ultra-high viscosity sodium alginate and ultra-high viscosity potassium alginate.

[0057] In a third aspect, the present invention provides a method for preparing a micro-expansion type internal curing agent, comprising the following steps:

[0058] (1) dissolving sodium thiosulfate in water to prepare a solution, and then adding alginate, polyacrylamide, and carboxymethyl cellulose ether into the solution and stirring to obtain a uniformly mixed viscose latex;

[0059] (2) adding sodium gluconate and sodium pyrosulfite to the viscose emulsion and stirring, and after dissolving, pouring into ethanol and stirring to obtain a viscose solution;

[0060] (3) Pour the solid sulfur ash powder into the pre-viscosity solution, continue stirring and let it stand;

[0061] (4) filtering the soaked solid sulfur ash powder, dehydrating and drying it to obtain a micro-expandable solid sulfur ash-based internal curing agent.

[0062] In a specific embodiment, the stirring condition of the solution in step (1) is 30-50° C. and continuous stirring for 1-2 hours;

[0063] The stirring condition of the solution in step (2) is to add sodium gluconate and sodium pyrosulfite and stir for 5 to 10 minutes, and after dissolution, pour into ethanol and stir for 10 to 40 seconds;

[0064] The stirring condition of the solution in step (3) is to stir for 20 to 50 minutes and then stand for 1 to 3 hours.

[0065] In a third aspect, the present invention provides a steel tube self-compacting concrete, comprising the following components in parts by mass: 350-450 parts of cement, 50-110 parts of fly ash, 10-30 parts of mineral powder, 20-40 parts of silica fume, 600-1000 parts of sand, 700-1200 parts of stone, 4-9 parts of admixture, and 30-60 parts of micro-expansive sulfur-fixing ash-based internal curing agent.

[0066] In a specific embodiment, preferably, the steel tube self-compacting concrete includes the following components in parts by mass: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, and 60 parts of micro-expansive sulfur-fixing ash-based internal curing agent.

[0067] Example 1

[0068] The embodiment of the present invention provides a steel tube self-compacting concrete, comprising the following raw materials in parts by mass: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, and 30 parts of micro-expansive sulfur-fixing ash-based internal curing agent.

[0069] Example 2

[0070] The embodiment of the present invention provides a steel tube self-compacting concrete, comprising the following components in parts by mass: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, and 60 parts of micro-expansive sulfur-fixing ash-based internal curing agent.

[0071] Comparative Example 1

[0072] This comparative example provides a steel tube self-compacting concrete, which includes the following raw materials in parts by weight: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, and 6 parts of admixture.

[0073] The difference between this comparative example and Example 2 is that no micro-expansive sulfur-fixing ash-based internal curing agent is added.

[0074] Comparative Example 2

[0075] The present comparative example provides a steel tube self-compacting concrete, comprising the following components in parts by mass: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, and 100 parts of micro-expansive sulfur-fixing ash-based internal curing agent.

[0076] The difference between this comparative example and Example 1 is that the amount of the micro-expansive sulfur-fixing ash-based internal curing agent added is 100 parts.

[0077] Comparative Example 3

[0078] The present comparative example provides a steel tube self-compacting concrete, comprising the following raw materials in parts by weight: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, and 60 parts of fixed sulfur ash.

[0079] The difference between this comparative example and Example 2 is that the internal curing agent is untreated solid sulfur ash.

[0080] Comparative Example 4

[0081] The present comparative example provides a steel tube self-compacting concrete, comprising the following raw materials in parts by weight: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, 5 parts of alginate, 0.5 parts of polyacrylamide, and 0.5 parts of carboxymethyl cellulose ether.

[0082] The difference between this comparative example and Example 2 is that the internal curing agent is replaced by a mixture of alginate, polyacrylamide and carboxymethyl cellulose ether.

[0083] Comparative Example 5

[0084] The present comparative example provides a steel tube self-compacting concrete, comprising the following raw materials in parts by weight: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, 30 parts of solid sulfur ash, 5 parts of alginate, 0.5 parts of polyacrylamide, and 0.5 parts of carboxymethyl cellulose ether.

[0085] The difference between this comparative example and Example 2 is that the internal curing agent is replaced by a mixture of solid sulfur ash, alginate, polyacrylamide and carboxymethyl cellulose ether.

[0086] The self-compacting concrete prepared in Examples 1 to 2 and Comparative Examples 1 to 5 was tested, and the compressive strength was tested with reference to GBT50081-2002 "Test Method for Mechanical Properties of Ordinary Concrete", the working performance was tested with reference to the relevant methods of GBT 50080-2016 "Test Method for Performance of Ordinary Concrete Mixtures", and the shrinkage performance was tested according to the relevant methods of GB / T 50082-2009 "Test Method for Long-term Performance and Durability of Ordinary Concrete", and the relevant performance test results are shown in Table 1 below.

[0087] Table 1

[0088]

[0089]

[0090] As can be seen from the above table, by comparing Example 1 with Comparative Example 1, it can be seen that the addition of the solid sulfur ash-based internal curing agent of the present invention can improve the compressive strength, collapse retention and early shrinkage of concrete. By comparing Example 2 with Comparative Example 2, it can be seen that when the amount of solid sulfur ash-based internal curing agent added is too large, the compressive strength of concrete will be reduced and the autogenous shrinkage will be increased. By comparing Experimental Example 2 with Comparative Example 3, it can be seen that although the addition of untreated solid sulfur ash can reduce the early shrinkage to a certain extent, it will cause the fluidity and compressive strength of concrete to be significantly reduced. It can be seen from the test results of Comparative Examples 4 and 5 that the addition of alginate, polyacrylamide, and carboxymethyl cellulose ether composition will reduce the fluidity and compressive strength of concrete. Therefore, it is explained that the addition of solid sulfur ash and alginate, polyacrylamide, carboxymethyl cellulose ether composition alone or directly mixed and added cannot improve the working performance, compressive strength and autogenous shrinkage of concrete.

[0091] The solid sulfur ash-based internal curing agent with an appropriate amount of the present invention can not only improve the compressive strength, fluidity and collapse resistance of concrete, but also reduce the autogenous shrinkage of concrete.

[0092] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A micro-expansion internal curing agent, characterized in that: The method comprises a sulfur-fixing ash and a viscose component, wherein the sulfur-fixing ash is immersed in a viscose solution so that the viscose component is coated on the surface and in the pores of the sulfur-fixing ash; The mass fraction of the viscose component in the viscose solution is 0.1% to 1%, and the viscose component includes 0 to 80 parts of alginate, 5 to 30 parts of polyacrylamide, and 0 to 20 parts of carboxymethyl cellulose ether.

2. A micro-expansion type internal curing agent according to claim 1, characterized in that: The viscose solution also includes sodium thiosulfate in a mass fraction of 0.1% to 3%.

3. A micro-expansion type internal curing agent according to claim 1, characterized in that: The viscose solution also includes ethanol with a mass fraction of 30% to 70%.

4. A micro-expansion type internal curing agent according to claim 1, characterized in that: The viscose solution also includes sodium gluconate in a mass fraction of 0.5% to 1%.

5. A micro-expansion type internal curing agent according to claim 1, characterized in that: The viscose solution also includes sodium pyrosulfite in a mass fraction of 0.1% to 0.8%.

6. A micro-expansion type internal curing agent according to claim 1, characterized in that: The mass ratio of the solid sulfur ash to the viscose solution is 1:50-100.

7. The method for preparing the micro-expansion type internal curing agent according to any one of claims 1 to 6, characterized in that: The steps include: (1) dissolving sodium thiosulfate in water to prepare a solution, and then adding alginate, polyacrylamide, and carboxymethyl cellulose ether into the solution and stirring to obtain a uniformly mixed viscose latex; (2) adding sodium gluconate and sodium pyrosulfite to the viscose emulsion and stirring, and after dissolving, pouring into ethanol and stirring to obtain a viscose solution; (3) Pour the solid sulfur ash powder into the pre-viscosity solution, continue stirring and let it stand; (4) filtering the soaked solid sulfur ash powder, dehydrating and drying it to obtain a micro-expandable solid sulfur ash-based internal curing agent.

8. The method for preparing the micro-expansion type internal curing agent according to claim 7, characterized in that: The stirring condition of the solution in step (1) is 30-50° C. and continuous stirring for 1-2 h; The stirring condition of the solution in step (2) is to add sodium gluconate and sodium pyrosulfite and stir for 5 to 10 minutes, and after dissolution, pour into ethanol and stir for 10 to 40 seconds; The stirring condition of the solution in step (3) is to stir for 20 to 50 minutes and then stand for 1 to 3 hours.

9. A steel tube self-compacting concrete, characterized in that: The invention comprises the following components in parts by weight: 350-450 parts of cement, 50-110 parts of fly ash, 10-30 parts of mineral powder, 20-40 parts of silica fume, 600-1000 parts of sand, 700-1200 parts of stone, 4-9 parts of admixture, and 30-60 parts of the internal curing agent according to any one of claims 1 to 6 or the micro-expanding sulfur-fixing ash-based internal curing agent prepared by the preparation method according to claim 7 or 8.

10. The steel tube self-compacting concrete according to claim 9, characterized in that: It includes the following components in mass parts: 400 parts of cement, 80 parts of fly ash, 20 parts of mineral powder, 30 parts of silica fume, 850 parts of sand, 940 parts of stone, 6 parts of admixture, and 60 parts of micro-expanding sulfur-fixing ash-based internal curing agent.

Citation Information

Cited By

  • Sodium alginate sealed semi-dry calcium-based desulfurized fly ash slow-release material as well as preparation method and application thereof

    CN120040019A